Batasan Syarat Calon Orang Tua Angkat Ditinjau Dari Prinsip The Best Interest Of The Child - Syaiful, Muhammad; Huda, Miftakhul (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2025)
Child adoption is a legal act aimed at providing protection and proper care for children, especially abandoned children. Government Regulation Number 54 of 2007 on the Implementation of Child Adoption establishes various requirements for prospective adoptive parents, including the condition of a minimum of 5 years of marriage. While this requirement aims to ensure the stability of adoptive parents' households, it is often considered too rigid and does not fully reflect the principle of the best interest of the child. This study aims to analyze the legal basis of such requirements and evaluate their alignment with the principle of the best interest of the child. The research employs normative legal methods using a statute approach and a conceptual approach. The findings reveal that although the 5-year marriage requirement seeks to safeguard the child's welfare, it often becomes a barrier for abandoned children to promptly receive care from suitable families. Therefore, an evaluation of the regulation is necessary to ensure flexibility in its application while prioritizing child protection. A reformulation of the policy, making it more adaptive and responsive to social dynamics, is expected to optimize the adoption process in Indonesia, thus effectively realizing the principle of the best interest of the child.